Spatial structure of yeast biofilms and the role of cell adhesion across different media - Irianto, Vichi Sicha; Plocek, Vítězslav; Bharti, Rashim; Maršíková, Jana; Váchová, Libuše; Palková, Zdena (Biofilm, 2025)
The ability of yeast cells to adhere to solid surfaces or even penetrate semi-solid surfaces and form multicellular biofilms are critical factors in infection. This study examines the relationship between cell adhesion capability and the ability to create spatially organized biofilms in selected Saccharomyces cerevisiae strains, including clinical isolates, and five Candida species (C. albicans, C. glabrata, C. krusei, C. parapsilosis, and C. tropicalis). We assessed cell adhesion to polystyrene surface in four media varying in source of carbon and other nutrients. Using microscopy of vertical cell arrangement profiles within yeast populations grown at the solid-liquid interface, we evaluated their internal organization to determine whether the populations exhibit typical biofilm characteristics, such as the spatial organization of distinct cell types. Results indicate that well adherent S. cerevisiae strains form spatial biofilms with typical internal organization, highlighting strain-specific responses to media composition and supporting the use of natural S. cerevisiae strains for biofilm research. Among Candida species, biofilm formation did not consistently align with adhesion efficiency to plastic; while C. albicans and C. krusei formed spatially structured biofilms on media where they adhered well, C. tropicalis and C. glabrata exhibited efficient adhesion without biofilm structuring. Interestingly, C. parapsilosis formed a structured biofilm despite minimal adhesion. These findings emphasize the role of media composition, particularly components of yeast extract and defined medium for mammalian cell growth RPMI, which differentially impacted adhesion and biofilm formation in S. cerevisiae and C. albicans.
Keywords: Microscopy; Adhesion; Biofilm; Yeast; Spatial structure